Research strategies for remote sensing development in Malaysia - Seeni Mohd., Mohd. Ibrahim; Hashim, Mazlan; Ahmad, Samsudin (2004)
Space technology is major strategic tool at present and in the future due to the uniqe global capabilities that it brings. It will help society overcome several threats to the quality of life on earth or even in human life itself. In that sense, space technology is fundamental to sustain security in all its form-political, economic, military, and ecological – in a truly global approach. In this paper, one aspect of space technology, i.e. remote sensing is addressed. It includes the current status of remote sensing technology and applications, some priority settings and implementation strategies.